How Speaking Confidence Correlates with Gender and English Proficiency in EFL Students - Sundari, Ayu; Syahid, Abdul; Mirza, Akhmad Ali (Universitas Pahlawan Tuanku Tambusai, 2025)
This study examines the connection between EFL students' speaking confidence, gender, and English competency. A speaking test and an English speaking confidence questionnaire were completed by 68 students (27 men and 41 females). Speaking confidence (p = 0.328) and gender (p = 0.379) had non-significant p-values, and regression analysis revealed that they only explained 2.6% of the variance in English proficiency (R2 = 0.026). Speaking confidence (t = 0.079, p = 0.937) and English proficiency (t = -0.877, p = 0.384) did not significantly differ between genders, according to t-tests. These results imply that other variables might have a greater impact on English proficiency. This study is important because it highlights the limited impact of gender and speaking confidence on EFL proficiency, prompting exploration of alternative factors and potentially more effective pedagogical approaches to enhance language acquisition.